1990
DOI: 10.1073/pnas.87.13.5061
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a mutated bovine growth hormone gene suppresses growth of transgenic mice.

Abstract: To determine the importance of the third a-helix in bovine growth hormone (bGH) relative to growthrelated biological activities, the following experimental approach was used: (i) mutagenesis ofhelix III of bGH to generate an idealized amphiphilic helix; (ii) in vitro expression analyses of the mutated bGH gene in cultured mouse L cells; (iii) mouse liver membrane binding studies ofwild-type and mutated bGH; and (iv) expression ofthe mutated gene in the transgenic mouse. An altered bGH gene (pBGHlOA6-M8) was ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
119
1
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(135 citation statements)
references
References 44 publications
12
119
1
3
Order By: Relevance
“…Data from in vitro GHR binding studies showed no significant difference between wild-type bGH and 3 D bGH in their GHR interactions, indicating that 3 D bGH had a binding affinity similar to wild-type GH. Surprisingly, however, when the gene encoding 3 D bGH analogue was expressed in transgenic mice, it resulted in growth retardation; the transgenic mice that expressed the mutated GH were significantly smaller compared with nontransgenic littermates (10). This result was contrary to the expectation that the 3 D bGH transgenic mice would be larger than normal.…”
Section: Structure -Function Relationship Of Ghcontrasting
confidence: 55%
See 2 more Smart Citations
“…Data from in vitro GHR binding studies showed no significant difference between wild-type bGH and 3 D bGH in their GHR interactions, indicating that 3 D bGH had a binding affinity similar to wild-type GH. Surprisingly, however, when the gene encoding 3 D bGH analogue was expressed in transgenic mice, it resulted in growth retardation; the transgenic mice that expressed the mutated GH were significantly smaller compared with nontransgenic littermates (10). This result was contrary to the expectation that the 3 D bGH transgenic mice would be larger than normal.…”
Section: Structure -Function Relationship Of Ghcontrasting
confidence: 55%
“…(Reprinted, with permission, from (2).) activation of the receptor (10). Structural studies then demonstrated that dual binding sites on hGH to two GHRs are required for receptor dimerisation and activation, which results in growth-promoting activities (7,8).…”
Section: Structure -Function Relationship Of Ghmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of highly specific antagonists of the GH action has recently been developed for the potential therapeutic use in various pathophysiological conditions, including diabetes. Initially it was shown that alteration of single amino acids in the third a-helix of bovine (b)GH (residues 109±126) results in a GH antagonist [68,69]. In vitro experiments showed that this new group of GH antagonists binds to the GH receptor with the same affinity as native GH but in vivo a phenotypic dwarf animal characterized by low circulating IGF-I concentrations and a proportional body composition develops when the GH antagonist is expressed in transgenic (TG) mice [68,69].…”
Section: Agents With Effects On the Altered Gh/igf Axis In Diabetic Kmentioning
confidence: 99%
“…Initially it was shown that alteration of single amino acids in the third a-helix of bovine (b)GH (residues 109±126) results in a GH antagonist [68,69]. In vitro experiments showed that this new group of GH antagonists binds to the GH receptor with the same affinity as native GH but in vivo a phenotypic dwarf animal characterized by low circulating IGF-I concentrations and a proportional body composition develops when the GH antagonist is expressed in transgenic (TG) mice [68,69]. Studies in long-term diabetic GH antagonist TG mice, that express the GH antagonist (bGH-G119R or hGH-G120R), have shown that these animals are protected against development of diabetic renal changes [70,71].…”
Section: Agents With Effects On the Altered Gh/igf Axis In Diabetic Kmentioning
confidence: 99%